Evaluation of the Addition of Bupivacaine to Intrathecal Morphine and Fentanyl for Postoperative Pain Management in Laparascopic Liver Resection. Issue 3 (1st April 2010) - Nguyen, Micheline; Vandenbroucke, Franck; Roy, Jean-Denis; Beaulieu, Danielle; Seal, Robert F.; Lapointe, Réal; Dagenais, Michel; Roy, André; Massicotte, Luc
Abstract : Background: Optimal modality of pain management after liver resection has been controversial. Epidural analgesia is often avoided because of transient coagulopathy and the associated risk of epidural hematoma. Single-dose intrathecal morphine has been shown to be an effective alternative in open liver resection. The purpose of this trial was to compare the analgesic efficacy of intrathecal morphine and fentanyl versus intrathecal bupivacaine 0.5%, morphine, and fentanyl for patients undergoing laparoscopic liver resection. Methods: This prospective randomized controlled double-blind trial compared morphine consumption between control (CTRL) group receiving a spinal injection of fentanyl 15 μg and morphine 0.4 mg and bupivacaine (BUPI) group receiving the same medications in addition to bupivacaine 0.5% (15 mg). Forty patients scheduled for laparoscopic liver resection were enrolled. Primary outcome was intravenous patient-controlled analgesia morphine consumption measured at 6, 9, 12, 18, 24, 36, and 48 hrs after spinal injection. Secondary outcomes were pain scores at rest and with movement, sedation, nausea, pruritus, and respiratory rate. Results: Cumulative doses of morphine were significantly lower for all time intervals in the BUPI group: 54 (30) versus 94 (47) mg ( P = 0.01) at 48 hrs. Morphine consumption was significantly lower for each time interval up to 18 hrs. Pain scores with movement were significantly lower in the BUPI group up to 24 hrs after injection. Pain score at rest was significantly lower in the BUPI group 9 hrs after injection. There were no differences in adverse effects. Conclusions: The addition of bupivacaine to intrathecal morphine and fentanyl significantly reduced intravenous morphine consumption after laparoscopic liver resection.